Association between masticatory dysfunction and gastroesophageal reflux disease: A population‐based study in the elderly. (19th December 2022) - Kuze, Luana Soares; Fornari, Fernando; Collares, Kauê; Della Bona, Alvaro
Abstract: Background: Caries and periodontal disease may cause tooth losses and chewing difficulty, especially in the elderly. Ingesting poorly chewed food may delay gastric emptying and favour the development of gastroesophageal reflux disease (GERD). Objective: This study investigated the association between masticatory dysfunction and GERD in the elderly from a rural area in southern Brazil. Methods: This census invited all 489 elderly from a city to participate. The study used a GERD symptoms questionnaire, followed by an oral examination. Masticatory dysfunction was analysed based on the chewing difficulty for some food groups. Tooth loss and chewing self‐perception were also considered as exposure variables. Poisson regression determined the association among variables by calculating the prevalence ratio [PR (95% confidence interval)]. Results: The response rate was 93.1% ( n  = 455, average age of 70.9 years, 50.5% men). The prevalence of GERD in this population was 36.9%. GERD was associated with chewing difficulty for vegetables (PR = 1.54), meats (PR = 1.34) and cereals (PR = 1.43) but not with poor chewing self‐perception (PR = 0.80) and tooth loss (PR = 1.22). GERD was also associated with xerostomia (PR = 1.63) and the female gender (PR = 1.35). Conclusion: Elderly people from a rural area with a reduced number of teeth present chewing difficulty and a high prevalence of GERD, indicating an association between GERD and masticatory dysfunction. Abstract :